Effect of different stocking densities on growth, oxidative stress, antioxidant enzymes, and hematological and immunological values of European catfish ( oct , 2023 , 10.1007/s10499-023-01306-1) - Koprucu, K.; Yonar, S. Mise; Koprucu, S.; Yonar, M. E. (Springer, 2024)
[Abstract Not Available]